Dragonflies and damselflies of New Zealand - Marinov, Milen (Milen G.) (Auckland University Press, 2019)
"This is a natural history and field guide to New Zealand's 14 species of dragonflies and damselflies ... Key features include: Expert and up-to-date information on the 14 species breeding in New Zealand; natural history of the group including an introduction to evolution, habitats, biology, behaviour, photography and conservation; more than 200 new photographs and hand-drawn illustrations of dragonflies and damselflies at all life stages in their environment; authoritative text on each species covering identification, measurement, behaviour, breeding, flying period and where to observe the species; range maps for all species"--Publisher information